Lesbian mothers' bids for normalcy in their children's schools - Bower, Laura A; Klecka, Cari L (The Educational Forum, 2009)
Albeit growing in number, lesbian mothers and their children remain a statistical minority in schools. Lesbian mothers in this study described their families as “normal” or “just like any other family.” From the perspective of queer theory, normal is a socially constructed and insidious concept. This study analyzes both the strategies participants used to be recognized as normal in their children’s schools and the reasons such recognition was perceived to be important by participants. © 2009 Taylor & Francis Group, LLC.
Keywords: dept.cur

(Re)Considering normal: queering social norms for parents and teachers. - Bower, Laura A; Klecka, Cari L (Teaching Education, 2009)
Recent debates regarding same-sex marriage and gay and lesbian adoption highlight the role of schools as sociopolitical institutions. Accordingly, teachers operating within social norms have considerable influence through their interactions with students and their families. Previous research points to lesbian, gay, bisexual, and transgender (LGBT) parents' frustrations with their children's schools, particularly as teachers resist representing LGBT families within curricula and fail to intervene when homophobic comments are made. Yet teachers' capacity to embrace diverse family structures while adhering to cultural expectations for teachers remains unexplored. This study, rooted in queer theory, explores the social norms teachers name for parenting in school settings and the way teachers position LGBT parents within these norms. Findings point to social norms for teachers and parents which indicate that teachers operate within heteronormative frameworks. They consider heterosexuality to be normal, while positioning LGBT identities as deviant. This is troubling given documented connections between teacher attitudes and parental involvement and between parental involvement and student achievement. Unchecked, heteronormative practices may result in inequitable school experiences for LGBT parents and their children. Teacher education must minimize heteronormativity through equipping teachers to attend to their own notions and assumptions regarding the intersection of parenting and sexual orientation. © 2009 Taylor & Francis.
Keywords: Teacher socialization; Teacher thinking and knowledge; dept.cur

The Ecology of Education: Knowledge Systems for Sustainable Development and Sustainability - Wensing, E J; Torre, Carlos Antonio (Journal of Teacher Education for Sustainability, 2009)
The Ecology of Education: Knowledge Systems for Sustainable Development and SustainabilityResearch in knowledge systems for sustainable development (KSSD) seeks to determine how science and technology can be put into effective action at a local level. Teachers in education for sustainability attempt to achieve the same goal. KSSD research has indicated that success is context driven, that panaceas are inappropriate and that knowledge systems at best provide solutions in evolution. In this paper, we describe a teaching framework that we are developing to support KSSD researchers and teachers in education for sustainability based in ecology of education. While a need for ecology in education may be apparent, there is concurrently an equally important need for ecology of education. We argue that one cannot teach ecology in education adequately without an appropriate ecology of education. This paper first explains why teachers need to know this and then describes how teachers of education for sustainability can implement and assess this approach in the classroom.
Keywords: dept.cur